PEMBUATAN VIRGIN COCONUT OIL DENGAN BANTUAN ENZIM BROMELAIN SEBAGAI ALTERNATIF PRAKTIKUM DI SMAN KAMPAR - Alwan Hendri; Fitri Refelita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
AbstractMaking coconut oil was usually done with heating coconut milk for hours until the protein in coconut milk broke and the oil can go out from coconut milk emulsion. The aim of this study was to determine the effect of pineapple juice addition against the amount of produced oil, to determine the quality of VCO enzymatic were density, water content, organoleptic (color, smell and flavor), teacher appraisal on work procedure and product of study result. The variation of pineapple juice shown that more pineapple juice addition then more produced VCO. The mount of produced oil for sample A 80 mL, sample B 83 mL and sample C 85 mL. The quality of three samples were for density which sample A 0.916, sample B 0.938, sample C 0.95. And for water content which sample A0.5, sample B 0.83 dan sample C 1.16. Between three sample, only sample A was accordance with SNI (Indonesia National Standard) No. 7381:2008 which for density was (0.91-0.92) and water content (0.1-0.5%). The teacher appraisal questionnaire about study result and appropriateness of VCO manufacture enzymatic gave cumulative value was 83.20% and it was in very good category.Keyword: VCO (Virgin Coconut Oil), Kelapa (Coconut nucifera L), Enzim Bromelain, Nanas (Ananas comosus L)